2016
DOI: 10.17511/ijpr.2016.i11.11
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile and antibiotic sensitivity pattern of neonatal sepsis in a tertiary care hospital of northern India

Abstract: Introduction: Neonatal sepsis is the single most important cause of neonatal deaths in the community. Objectives: To identify the common bacterial pathogens associated with neonatal sepsis and to identify their antibiotic sensitivity pattern. Material and Methods: During the study period, all the neonates admitted in neonatology ward were screened for sepsis by physical examination and clinical features. All infants satisfying the criteria for sepsis were subjected for blood culture. Growths, if any were noted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Our incidence of culture-positive neonatal sepsis was found to be 19 per 1000 neonatal admissions or 1.90% of total admissions. In a recent study from India, a higher incidence of 35.5/1000 admissions was reported [ 11 ]. Lu et al reported a much comparable rate of 10.5 per 1000 admissions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our incidence of culture-positive neonatal sepsis was found to be 19 per 1000 neonatal admissions or 1.90% of total admissions. In a recent study from India, a higher incidence of 35.5/1000 admissions was reported [ 11 ]. Lu et al reported a much comparable rate of 10.5 per 1000 admissions [ 12 ].…”
Section: Discussionmentioning
confidence: 99%